The Influence of Population Size, Economic Growth, Human Development Index, Unemployment on Poverty in Indonesia from 1998 to 2022 - Diniati, Bintis Ti’anatud; Permana, Dimas Arya (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research is motivated by the large number of people still living below the poverty line, especially in developing countries experiencing high economic growth that inadequately benefits the poor population. Poverty is a multidimensional issue. Therefore, poverty alleviation efforts need to be comprehensive, covering various aspects of community life and executed in an integrated manner. The objectives of this research are to determine: (1) The Influence of Population Size on poverty in Indonesia, (2) The Influence of Economic Growth on poverty in Indonesia, (3) The Influence of Human Development Index (HDI) on poverty in Indonesia, and (4) The Influence of Unemployment on poverty in Indonesia. This research employs an associative quantitative method using secondary data sources. The collected data are then analyzed using Vector Error Correction Model (VECM). The research findings indicate that, based on the VECM estimation test in the long run, the Population Size variable has a negative and significant effect on Poverty. Meanwhile, the Economic Growth variable has a positive and significant effect on Poverty. As for the Human Development Index (HDI) variable, it has a negative and significant effect on Poverty. However, the Unemployment variable has a negative and insignificant effect on Poverty